Audit internal dan praktik (sesuai international standards for the professional practice of internal auditing 2013) /Faiz Zamzami, Ihda Arifin Faiz, Mukhlis - FAIZ ZAMZAMI; Ihda Arifin Faiz; Mukhlis (Gadjah Mada University Press, 2015)
xii, 211 hlm. : ilus. ; 23 cm.